ANALISIS PENGGUNAAN APLIKASI TIK TOK TERHADAP PERUBAHAN PERILAKU SISWA SD N 31 PALEMBANG - Sefta Azzahra; Dessy Wardiah; Aldora Pratama (STKIP Subang, 2023)
This study aims to describe changes in student character and student attitudes in PKN learning at SD N 31 Palembang. This research is a type of qualitative descriptive approach with a descriptive method. The data obtained through this study are observations, interviews, and documentation. Data was analyzed using components recommended by Miles and Huberman. The subjects of this study were teachers and students of SD N 31 Palembang totaling 6 students of SD Negeri 31 Palembang.The research instrument used in this study is non- test, namely in the form of observation, interview or interview. Data collection is carried out in the morning after the collected data is immediately analyzed. Based on the results of the study, it shows that the use of the Tik Tok application at SD Negeri 31 Palembang seen from the aspect of observation based on changes in student behavior on average 6 students of SD Negeri 31 Palembang is said to be good and in accordance with what is in theoretical studies. That the results of this study show the use of the Tik Tok application for changes in student behavior in PKN learning can be categorized as good. Keywords: The use of the Tik Tok application to change student behavior